The Relationship Between Spiritual Health and Moral Sensitivity in Nursing Students of Hamadan University of Medical Sciences, 2017 - Morteza Shamsizadeh; Khodayar Oshvandi; kamran alipor; Soraya Moamer; Zahra Maghsoudi (Hamadan University of Medical Sciences, 2020)
Background & Aim: Professional practice in nursing requires familiarity with the ethical issues of nursing profession and their sensitivity to patients. This sensitivity, as the basis of nursing ethics, should be considered from the beginning of nursing education. The degree of adherence to one's religion and the level of one's beliefs appear to be factors influencing moral sensitivity. The purpose of this study was to determine the relationship between spiritual health and moral sensitivity of nursing students. Methods: In this descriptive-analytical study, 123 nursing students of Hamadan University of Medical Sciences were enrolled. Data were collected through questionnaire demographic information, Poultzan and Erison spiritual health questionnaire and moral sensitivity questionnaire. The data were analyzed by Chi-square and Pearson correlation coefficients using SPSS 21 software. Results: The mean age of participants was 23.69±4.55 years. Most nursing students had moderate spiritual health score and moral sensitivity. There was a positive and significant correlation between spiritual well-being with nursing students 'moral sensitivity (r=0.26, P=0.003), meaning that the higher the students' spiritual health score, the higher their moral sensitivity. Conclusion: The results showed that spiritual health is an important parameter in promoting the moral sensitivity of nursing students. Therefore, promoting religious beliefs improves the health status of students and thus plays an important role in the implementation of effective patient care. In the promotion of their health, the spiritual aspect should also be taken into consideration.